Adenosine transport in peripheral blood lymphocytes from Lesch-Nyhan patients. - Torres, Rosa J (2004)
We postulated that adenosine function could be related to some of the neurological features of Lesch-Nyhan syndrome and therefore characterized adenosine transport in PBLs (peripheral blood lymphocytes) obtained from Lesch-Nyhan patients (PBL(LN)) and from controls (PBL(C)). Adenosine transport was significantly lower in PBL(LN) when compared with that in PBL(C) and a significantly lower number of high affinity sites for [(3)H]nitrobenzylthioinosine binding were quantified per cell ( B (max)) in PBL(LN) when compared with that in PBL(C). After incubation with 25 microM hypoxanthine, adenosine transport was significantly decreased in PBL(LN) with respect to PBL(C). Hypoxanthine incubation lowers [(3)H]nitrobenzylthioinosine binding in PBL(C), with respect to basal conditions, but does not affect it in PBL(LN). This indicates that hypoxanthine affects adenosine transport in control and hypoxanthine-guanine phosphoribosyltransferase-deficient cells by different mechanisms.